Stylistic deviation and Pakistani idiom: creative use of English in Moni Mohsin’s Duty Free - Riaz, Mehvish (Creativity Studies, 2022)
The study highlights the creative use of deviation as a stylistic device for presenting linguistic innovations in the novel Duty Free (originally published in 2011) written in English by a Pakistani writer Moni Mohsin. It has been explored how and to what extent the eight types of deviation, such as lexical, grammatical, semantic, phonological, graphological, dialectal, deviation of register, and deviation of historical period suggested by Geoffrey N. Leech have been employed by Moni Mohsin in her novel. By identifying how morphological, compound, and idiomatic neologisms have been created, words from native languages have been borrowed, and innovative similes, metaphors, and tautologies rooted in Pakistani culture have been employed, the study helps in understanding the extent to which novel uses of English language create unique stylistic effects, add to the richness and vitality of English, and cause variation simultaneously. Deviation of historical period and certain subcategories of phonological deviation have not been found. The study has implications for Pakistani English, lexicology, stylistic foregrounding, and creative writing in English.